Local governance in Uganda: Adminstrative law and governance project, Kenya, Malawi and Uganda - Nakayi, Rose (IDRC, 2018)
The paper reviews how principles of administrative law play out in day to day practices of officers at the local governance level in Uganda, and looks at what kinds of citizen participation can shape decision making, outcomes, actions and processes within local government. A constrained financial environment tends to make citizens reliant on central government; the same lack of engagement can justify and feed corruption and bribery of leaders not guided by the people’s will. Judicial review may be a tool for good local governance if it is successfully resorted to, and where people are aware that there is an existing legal mechanism.